(untitled) (Siddhajyoti Interdisciplinary Journal, 2025)
The teachers teaching English and Principle of Management at the constituent college and affiliated colleges of Purbanchal University were interviewed to identify and enhance the English language efficiency of Bachelor of Business Administration (BBA) students. As such, this paper presents strategies for improving English language of students at Purbanchal University School of Management. Besides, the paper also highlights this dual strength of the Nepali language and English language for learning and understanding lessons and or any topic outside the classroom.